2013
DOI: 10.1096/fj.13-235382
|View full text |Cite
|
Sign up to set email alerts
|

AKT3 controls mitochondrial biogenesis and autophagy via regulation of the major nuclear export protein CRM‐1

Abstract: Our previous work has shown that Akt3 is required for mitochondrial biogenesis in primary human endothelial cells (ECs) and in Akt3-null mice; Akt3 affects subcellular localization of peroxisome proliferator-activated receptor γ coactivator-1 (PGC-1α), the master regulator of mitochondrial biogenesis. The purpose of this study is to determine the mechanism by which Akt3 controls the subcellular distribution of PGC-1α and to explore the effect on mitochondrial biogenesis and turnover during angiogenesis. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 56 publications
(69 reference statements)
0
47
0
Order By: Relevance
“…Additional studies are reporting potential nuclear functions of Akt3, including Ago2-mediated translational repressive activities (28), transcriptional control of IGFBP3 in lung cancer cells (29), and ERBB2, ERBB3, and ERα in breast tumor cells from a mouse transgenic model (30). Although these effects are likely mediated by multiple complex systems, Akt3 has been reported to control the stability of the major nuclear export protein, chromosome maintenance region-1 (CRM-1), leading to altered mitochondrial biogenesis and autophagy (31). It is plausible that Akt3 may regulate other biological processes via similar mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Additional studies are reporting potential nuclear functions of Akt3, including Ago2-mediated translational repressive activities (28), transcriptional control of IGFBP3 in lung cancer cells (29), and ERBB2, ERBB3, and ERα in breast tumor cells from a mouse transgenic model (30). Although these effects are likely mediated by multiple complex systems, Akt3 has been reported to control the stability of the major nuclear export protein, chromosome maintenance region-1 (CRM-1), leading to altered mitochondrial biogenesis and autophagy (31). It is plausible that Akt3 may regulate other biological processes via similar mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Limited studies on Akt3 showed that it is required for VEGF stimulation of mitochondrial biogenesis and autophagy in endothelial cell, and is important for growth-factor induced angiogenic responses (32). Akt3 is the dominant isoform in melanoma and ovarian cancer and regulates cellular senescence, VEGF secretion and angiogenesis in these tumors (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Stem cells also help in dental cares by inducing regeneration or differentiation of dental epithelia into enamel-producing ameloblasts [86]. MSCs implanted in pancreas can replace defective islet beta cells, enhance β-cell proliferation [87], cure type 1 diabetes [88] and do its reversal [89,90,98,99] in non-obese diabetic mice [91,92]. Similarly, implantation of multipotent stem cells implanted in bone marrow can suppress ovarian cancer and stop metastasis [90,92].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Endothelial cells (ECs) show wider therapeutic potential in cardiovascular [94,95], Parkinson's disease [95,96], and neurological diseases [97]. These cells do immune regulation of T lymphocyte cells [93,98] and induce mitochondrial biogenesis in primary human endothelial cells (ECs) and in Akt3-null mice [89,99]. MSCs are used in regenerative medicine, for wound healing, tissue regeneration and transplantation of organs and therapeutic care of autoimmune diseases ( Table 1).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
See 1 more Smart Citation